Perbandingan Hasil Belajar Menerapkan Model Cooperative Learning Team Assisted Individualization (TAI) dan Course Review Horay dengan Konvensional Pada Mata Pelajaran Ekonomi Kelas XI SMA Negeri 3 Solok - Citra Alvia Nora Harahap; Annur Fitri Hayati (Jurnal Ecogen, 2020)
This research aims to: difference learning outcomes using cooperative learning model type Teams Assisted Individualization And Model Type Course Review Horray With Conventional At Class XI  SMA N 3 Solok. The research used a quasi-experimental design, the technique is purposive sampling, the instrument trials, gain score, validity, reliability, different test problem, and difficulty levels. Data collection by documentation and test result of learning outcome. The population in this study is XI SMA N 3 Solok and the sample is XI IPA 4 and XI IPA 5 for class experiment and XI IPA 3 for class control. The analytical method used a paired sample t-test and independent sample-test analysis. The result is: there are differences a  student learning outcomes using cooperative learning model  Team Assisted Individualization and Course Review Horray with conventional economic subjects in class XI  SMA N 3 Solok based on calculation with Sig. value of 0,000. Keywords: model team assisted individualization, course review horay learning outcomes